MBTI personality type and financial behavioral bias - Effendi, Kharisya Ayu; Amalia, Shendy (International Journal of Social and Administrative Sciences, 2024)
Studies on behavioral financial theory found that the individual investment decision process involves many behavioral biases. This behavioral bias can cause investors to deviate from rational decision-making. The purpose of this study is to see whether there is an influence of gender factors on financial behavioral biases in this study, namely overconfidence bias, herding, and regret aversion. Then this study also aims to see whether MBTI personality types influence financial behavioral biases in this study, namely overconfidence bias, herding, and regret aversion. This study aims to identify the relationship between gender variables, MBTI personality assessments, and financial behavioral biases in investors in Indonesia. To conduct this study, a structured questionnaire was given to 230 respondents at the researcher.populix.co.id as the primary data collection page that includes questions related to gender variables, overconfidence bias, herding bias, regret aversion bias, and MBTI personality assessment. Of the 230 respondents, 182 respondents were accepted and met the analysis requirements. The findings obtained were that the gender factor that had a significant effect on this study was only on overconfidence bias while herding and regret aversion did not have a significant effect. Then the MBTI personality type significantly influenced the three financial behavior biases.